Elusive Peace in Afghanistan: Taliban Control More Territory - Sajjad Ashraf (2015)
The capture of Kunduz in northern Afghanistan shows the Taliban ability to strike at urban centres away from their southern strongholds. The Afghan government is dependent on the continued presence of US forces and peace remains elusive.